2011
DOI: 10.1109/tvcg.2011.167
|View full text |Cite
|
Sign up to set email alerts
|

Arc Length-Based Aspect Ratio Selection

Abstract: The aspect ratio of a plot has a dramatic impact on our ability to perceive trends and patterns in the data. Previous approaches for automatically selecting the aspect ratio have been based on adjusting the orientations or angles of the line segments in the plot. In contrast, we recommend a simple, effective method for selecting the aspect ratio: minimize the arc length of the data curve while keeping the area of the plot constant. The approach is parameterization invariant, robust to a wide range of inputs, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 12 publications
1
21
1
Order By: Relevance
“…We establish the connection between AL and the principle of banking to 45 • and derive the upper and lower bounds of its produced averaged absolute slopes. Finally, we conduct a comprehensive quantitative comparison between the five methods AL, AWO, RV, MS, MLC, with similar experimental setting of Talbot et al [15]. Our results contribute to the understanding of aspect ratio selection methods in three aspects: first, we show that AWO always performs similarly to AL, while MS is not.…”
Section: Introductionsupporting
confidence: 54%
See 2 more Smart Citations
“…We establish the connection between AL and the principle of banking to 45 • and derive the upper and lower bounds of its produced averaged absolute slopes. Finally, we conduct a comprehensive quantitative comparison between the five methods AL, AWO, RV, MS, MLC, with similar experimental setting of Talbot et al [15]. Our results contribute to the understanding of aspect ratio selection methods in three aspects: first, we show that AWO always performs similarly to AL, while MS is not.…”
Section: Introductionsupporting
confidence: 54%
“…They also found that the orientation resolution is maximized when the average orientation between them is 45 • . Based on these two observations, Cleveland et al [1,2,3] and the following Heer and Agrawala [6] as well as Talbot et al [15] proposed a few methods for aspect ratio selection with different properties, see Table 1.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Following Bertin, researchers in multiple disciplines have conducted human subjects experiments [6,14,21,24,37,38,46] and proposed perceptuallymotivated rankings of visual variables for nominal, ordinal or quantitative data [6,24,25,27,36]. Researchers have also investigated how different choices of design parameters such as aspect ratio [5,13,42], chart size [16,23], axis labeling [43] and animation design [17,29] influence the effectiveness of graphs. This work typically compares the effectiveness of alternative visual variables.…”
Section: Graphical Perceptionmentioning
confidence: 99%
“…Even today these line charts are among the most popular time series visualization techniques and their details are actively discussed in the visualization community, as for example the arc length-based aspect ratio selection [31]. Furthermore, visualization techniques such as stacked graphs (e.g.…”
Section: Time Series Visualization Techniquesmentioning
confidence: 99%